The Effect of Hypertension on Cognitive Decline and Dementia: A Meta- Analysis - Ahmed, Maryam Mohammed Ali; Kowayer, Jamila Saeed Ahmad Bin; Lootah, Amna; Alhammdi, Sara Ibrahim; Alshamsi, Fatima Ahmed Sultan; Almheiri, Maha; Ali, Reem Ibrahim; Alhosani, Abeer; Skheta, Hana Abdelnaser; Hussein, Israa Fouad Elsayed Farag (Cardiology and Cardiovascular Medicine, 2025)
Hypertension is known to be a risk factor for cardiovascular diseases, but its relationship with cognitive impairment and dementia is an emerging area of study. This meta-analysis intends to examine the relationship between hypertension and cognitive impairment by combining data from several studies in an attempt to establish the level of correlation. The studies in the analysis include longitudinal cohort studies, case-control studies, and randomized controlled trials (RCTs) that look at cognitive outcomes in different domains, such as global cognition, executive function, memory, and attention. According to studies regarding hypertension, patients suffering from it showed a much higher risk score (38%) of cognitive impairment than normotensives. Furthermore, it has been noted that midlife Hypertension (ages 40-65) has the worst effect on late-life dementia compared to most late-life hypertension. There are some variations as late-life hypertension appears to be less strongly associated with risk, suggesting some form of disease-modifying interaction. Mechanistically, cognitive decline impairment due to hypertension can be attributed primarily to cerebrovascular damage, neuroinflammation, increased oxidative stress, and amyloid pathologies causing neurodegeneration and hyper-susceptibility to dementia. This research constitutes a further examination of cognition decline in the context of the effects of anxiety hypertension treatment. ACE inhibitors and calcium channel blockade drugs are believed to have some degree of neuroprotection by increasing cerebral blood flow and lowering inflammatory processes, which could lead to neurocognitive disorders. This meta-analysis adds to the evidence of hypertension as a new risk factor for dementia and cognitive decline; thus, it necessitates such risk assessment at early stages, lifestyle changes and optimal pharmacotherapy. Such initiatives must strive to foster adherence to treatment, recognition of hypertension, and the definition of the cognitive domain in the broader cardiovascular risk framework for dementia prevention.